A rational approach to choosing a reactive power compensation device - Leonova Yu.Yu.; Negadaev V.A. (Горное оборудование и электромеханика, 2025)
The increase in the cost of energy resources makes it necessary to take into account measures to reduce non-production losses of electricity when building an electricity supply network. It is possible to reduce power losses by increasing the power factor. Despite a significant amount of research on the optimization of methods for selecting reactive power compensation devices, their placement and management, the installation costs of such devices are often determined approximately, without taking into account the nature of the dependencies between cost and their parameters. This article presents the results of research on the dependence of the cost of reactive power compensation devices on their parameters: reactive power, permissible current and capacitance. To clarify the nature of the relationship between the cost of capacitor banks and the value of reactive power, regression equations describing this relationship (in prices of 2023) are defined. The method of correlation analysis is used to find the regression equations. Based on the value of the Fisher criterion, a regression equation was chosen that best describes the relationship between the specified parameters of capacitor banks. The use of a deflator index to predict the cost of capacitor banks is proposed. To determine the values of the reactive power of a capacitor bank, at which it is advisable to turn on capacitors through a step-up transformer, the cost of reactive power compensation methods at reactive power values of 50 kVAr and above and a comparison of reactive power compensation methods using a step-up transformer and without its use was carried out. Based on the results of the study, conclusions were drawn: on the existence of a relationship between the cost of capacitor banks and reactive power, described by a polynomial regression equation; on the influence of voltage values on the cost of a unit of capacitance of capacitor banks. It is noted that if the required reactive power exceeds the value of 300 kVAr, it is advisable to consider switching on static capacitors using a step-up transformer.